DIAGNOSIS OF FUNDOPLICATION CUFF FAILURE IN PATIENTS OPERATED BY THE NISSEN METHOD - V. K. Koryttsev; S. V. Dergal; E. V. Frolova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2021)
The article is devoted to the treatment of patients with hiatal hernia. The aim of the study was to develop a method for diagnosing the failure of the  fundoplication cuff in patients with recurrent hernia of the foodwater orifice of  the diaphragm after Nissen fundoplication. The study included 42 patients. The  first group consisted of 16 people with recurrent hiatal hernia. The second  group consisted of 26 people without recurrence of hiatal hernia. When comparing groups of patients, a simple and objective sign of the failure of the fundoplication cuff after Nissen surgery is described.